KINERJA GURU PAI DALAM PELAKSANAAN PEMBELAJARAN DI MTS SE-KOTA PAGAR ALAM - Nurfarida Nurfarida (IAIN Bengkulu, 2020)
Performance of Teachers PAI In Implementation Learning In MTs Se-Pagar Alam (Study Between Master certifica- tion with a Non-Certified Teacher). This research uses quantitative and comparative approach. Population and sample in this research are all teachers of Islamic Religious Education either certified or not certified in MTs Se-Pagar natural city which amounts to 31 teachers of Islamic Education. The data collection technique is done by using questionnaire method used to ob- tain data about the performance of Islamic Religious Education teacher, the method of observation is done to know the process of learning by the teacher in class, the method of documentation is done to obtain data about the teacher, while the validity test used is the validity test of the correlation formula product Moment, while to test reliabel using Cromach Alpa analysis formula used in the form of statistical analysis by using t-test formula. Based on the result of t-test analysis, there are significant differ- ences in the performance of teachers of Islamic Religion certification and non certification